Can Eye-tracking Technology Improve Situational Awareness and Student Feedback During Simulation? Final Report. - Cooper, Simon; Browning, Mark; Ross, Linda; Sparkes, Louise; Williams, Brett; Munro, Graham; O'Meara, Peter; Black, Barbara; Bogossian, Fiona (Office for Learning and Teaching, 2014)
Situation awareness is a crucial factor in the management of emergencies and effective feedback techniques are a core component in simulation education. This is the final report from a project that evaluated the effectiveness of eye tracking technology for improving feedback and situation awareness for nursing/paramedic students, and developed guidelines and resources for best practice with this new technology. In simulated scenarios the project used innovative eye tracking techniques, situation awareness measures, photo-elicitation (reflective review), and student evaluations.